Data mining for business analytics : concepts, techniques, and applications with JMP Pro /: concepts, techniques, and applications with JMP Pro. (2016) - Shmueli, Galit, 1971-; Bruce, Peter C; Stephens, Mia L; Patel, Nitin R
No abstract available